(untitled) (Nexo Revista Científica, 2023)
This work presents the effect of using pitahaya mucilage and linseed polymer as a viscosity-modifying admixture in the preparation of self-compacting concrete. Two types of cements and solutions containing natural additives at two concentrations were used. Cylindrical specimens of 100 mm in diameter x 200 mm of high were cast, whit moist cured for 7 and 28 days. Compressive strength, Ultrasonic Pulse Velocity and porosity were evaluated at different ages. The results showed that the concretes containing linseed polymer present a higher compressive strength compared with the rest of the mixtures. The porosity of the concretes with organic additions was higher compared to the control.